PRODUCT COSTING IN THE SALES CONFIGURATOR - Ranta, Eero (My University, 2015)
The purpose of this thesis isto research how case company’s product costing should be organized in the sales configurator environment. The research problem is divided to three separate sections. The first section covers the costing model which could be used to calculate product costs in the sales configurator environment. The suggestion for instance takes a stance on what kinds of costs are assigned to individual product and what are the allocation methods. The second section deals with question how the suggested costing model should be maintained. The last section for its part discusses that can the sales configurator environment be used as a tool to control products’ cost knowledge. The literature survey introduced the principles of product costing and diverse number of different costing system which can be used to calculate product specified costs. Costing systems differed from each other’s significantly due to various allocation methods and accuracies. The empiricism part of the thesis consisted of research on the present costing models that are used in the sales configurator environment. The information was gathered from three sources that are internal documents, the actual sales configurator environment and unstructured interviews with employees who use sales configurator in their everyday work. Based on the literature survey and the research on the current state, previously presented research problems were answered. The suggestion of the future costing model was based on one current model. It assigned to product only manufacturing costs and ignores non-manufacturing costs. The main idea of the maintenance process was that each production unit carries the responsibility of pricing their own products. During the research it could be observed that there was a significant demand for a so called cost databank and it was rational to use sales configurator environment for this purpose because cost knowledge needed to be anyhow input and maintained in the sales configurator environment.
Keywords: product costing; sales configurator; cost assignment; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|